Structural and bioactive characteristics of a dextran produced by Lactobacillus kunkeei AK1 - Yilmaz, Mustafa Tahsin; Ispirli, Humeyra; Taylan, Osman; Bilgrami, Anwar L.; Dertli, Enes (ELSEVIER, 2022)
In this study, structural and techno-functional characteristics of an exopolysaccharide (EPS) produced by Lactobacillus kunkeei AK1 were determined. High-performance liquid chromatography (HPLC) analysis demonstrated that EPS AK1 was composed of only glucose units. H-1 and C-13 Nuclear magnetic resonance (NMR) analysis revealed that EPS AK1 was a dextran type EPS containing 4.78% (1 -> 4)-linked alpha-D-glucose branches. The molecular weight of EPS AK1 was determined to be 45 kDa by Gel Permeation Chromatography (GPC) analysis. A high level of thermal stability up to 280 degrees C was determined for dextran AK1 detected by Differential scanning calorimetry (DSC) and Thermogravimetric analysis (TGA). Dextran AK1 appeared as regular spheres with compact morphology and as irregular particles in the solution with no clear cross-linking between the chains of the polysaccharide observed by Scanning electron microscopy (SEM) and Atomic force microscopy (AFM) analysis, respectively. X-ray diffraction analysis (XRD) analysis demonstrated that dextran AK1 had a crystalline structure. A relatively strong antioxidant activity was observed for dextran AK1 determined by 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2'-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) radical scavenging and cupric reducing antioxidant capacity (CUPRAC) tests. Finally, only a digestion ratio of 3.1% was observed for dextran AK1 following the in vitro simulated gastric digestion test.
Keywords: Lactobacillus kunkeei; Dextran; LAB; Exopolysaccharides; Structural and bioactive characteristics; LACTIC-ACID BACTERIA; PHYSICOCHEMICAL CHARACTERIZATION; GLUCAN; EXOPOLYSACCHARIDE; GLUCANSUCRASE; SOURDOUGH; ENZYMES; OLIGOSACCHARIDES; REUTERANSUCRASE; FERMENTATION; Biochemistry & Molecular Biology; Chemistry; Polymer Science